Drosophila p53 integrates the antagonism between autophagy and apoptosis in response to stress. Issue 5 (4th May 2019) - Robin, Marion; Issa, Abdul Raouf; Santos, Cristiana C.; Napoletano, Francesco; Petitgas, Céline; Chatelain, Gilles; Ruby, Mathilde; Walter, Ludivine; Birman, Serge; Domingos, Pedro M.; Calvi, Brian R.; Mollereau, Bertrand
ABSTRACT: The tumor suppressor TP53/p53 is a known regulator of apoptosis and macroautophagy/autophagy. However, the molecular mechanism by which TP53 regulates 2 apparently incompatible processes remains unknown. We found that Drosophila lacking p53 displayed impaired autophagic flux, higher caspase activation and mortality in response to oxidative stress compared with wild-type flies. Moreover, autophagy and apoptosis were differentially regulated by the p53 (p53B) and ΔNp53 (p53A) isoforms: while the former induced autophagy in differentiated neurons, which protected against cell death, the latter inhibited autophagy by activating the caspases Dronc, Drice, and Dcp-1. Our results demonstrate that the differential use of p53 isoforms combined with the antagonism between apoptosis and autophagy ensures the generation of an appropriate p53 biological response to stress.